"It's something that marks you": Abortion stigma after decriminalization in Uruguay - Roosbelinda Cárdenas; Ana Labandera; Sarah E. Baum; Fernanda Chiribao; Ivana Leus; Silvia Avondet; Jennifer Friedman (BMC, 2018)
Abstract Background Abortion stigma is experienced by women seeking abortion services and by abortion providers in a range of legal contexts, including Uruguay, where abortion was decriminalized up to 12 weeks gestation in 2012. This paper analyzes opinions and attitudes of both abortion clients and health professionals approximately two years following decriminalization and assesses how abortion stigma manifests among these individuals and in institutions that provide care. Methods In 2014, we conducted twenty in-depth, semi-structured interviews with abortion clients (n = 10) and health care professionals (n = 10) in public and private facilities across Uruguay's health system. Interviews were recorded, transcribed, and then coded for thematic analysis. Results We find that both clients and health professionals express widespread satisfaction with the implementation of the new law. However, there exist critical points in the service where stigmatizing ideas and attitudes continue to be reproduced, such as the required five-day waiting period and in interactions with hospital staff who do not support access to the service. We also document the prevalence of stigmatizing ideas around abortion that continue to circulate outside the clinical setting. Conclusion Despite the benefits of decriminalization, abortion clients and health professionals still experience abortion stigma.